2022
DOI: 10.5194/acp-22-14467-2022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of model and ground observations finds snowpack and blowing snow aerosols both contribute to Arctic tropospheric reactive bromine

Abstract: Abstract. Reactive halogens play a prominent role in the atmospheric chemistry of the Arctic during springtime. Field measurements and modeling studies suggest that halogens are emitted into the atmosphere from snowpack and reactions on wind-blown snow-sourced aerosols. The relative importance of snowpack and blowing snow sources is still debated, both at local scales and regionally throughout the Arctic. To understand the implications of these halogen sources on a pan-Arctic scale, we simulate Arctic reactive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 117 publications
1
25
0
Order By: Relevance
“…SSA influence radiative forcing and therefore climate both directly by absorbing and scattering sunlight and indirectly by modifying the reflectivity, emissivity, lifetime, and extent of clouds (DeMott et al., 2016; O’Dowd et al., 1997; Struthers et al., 2011). Furthermore, SSA likely play an important role in polar tropospheric ozone and halogen chemistry through the release of active bromine in polar spring which contributes to ozone depletion events (ODEs) (e.g., Choi et al., 2018; Huang et al., 2020; Kalnajs et al., 2013; Marelle et al., 2021; Swanson et al., 2022; Yang et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…SSA influence radiative forcing and therefore climate both directly by absorbing and scattering sunlight and indirectly by modifying the reflectivity, emissivity, lifetime, and extent of clouds (DeMott et al., 2016; O’Dowd et al., 1997; Struthers et al., 2011). Furthermore, SSA likely play an important role in polar tropospheric ozone and halogen chemistry through the release of active bromine in polar spring which contributes to ozone depletion events (ODEs) (e.g., Choi et al., 2018; Huang et al., 2020; Kalnajs et al., 2013; Marelle et al., 2021; Swanson et al., 2022; Yang et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…1; Hermann et al, 2019). Some model studies were able to explain major depletion events in simulations by introducing the wind-induced release of bromine from the snowpack and have shown that both blowing snow and the snowpack are important sources of bromine during the spring (e.g., Yang et al, 2010;Toyota et al, 2011;Yang et al, 2020;Huang et al, 2020;Swanson et al, 2022). Figure 2 shows the vertical extent of low O 3 episodes observed by lidar at Eureka in northern Canada.…”
Section: Ozone Sinksmentioning
confidence: 99%
“…Hourly output of surface layer O 3 and profiles of BrO from GEOS-Chem simulations are sampled along the O-Buoy tracks at the closest time to each MAX-DOAS measurement. Columns of BrO 200m and BrO LT are determined from modeled profiles of BrO following the method presented by Swanson et al (2022). For each time step along the buoy track, partial columns of modeled BrO are calculated along the vertical resolution of the MAX-DOAS averaging kernels.…”
Section: Autonomous Ice-tethered Buoy Measurementsmentioning
confidence: 99%
“…Columns of BrO 200m and BrO LT are determined from modeled profiles of BrO following the method presented by Swanson et al. (2022). For each time step along the buoy track, partial columns of modeled BrO are calculated along the vertical resolution of the MAX‐DOAS averaging kernels.…”
Section: Model and Measurement Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation